PP.55 Screening Women for Asymptomatic Bacteriuria in Early Pregnancy May Reduce the Risk of Low Birth Weight. (26th April 2013) - Browne, HE; Bonney, EA; McDowell, LA; Young, J; Simpson, NAB
Abstract : Introduction: Anatomical changes in pregnancy predispose women to asymptomatic bacteriuria (ASB). Current NICE guidance in the UK advises that a mid-stream urine (MSU) sample should be offered in early pregnancy to screen for and treat ASB. Aims: To investigate how many women currently have an MSU in early pregnancy (<18 weeks gestation) in an inner-city maternity unit; to evaluate whether current screening practise affects pregnancy outcome. Methods: This was a retrospective cohort study which examined notes of all delivered women who gave birth within a three-week period. Appropriate parametric and non-parametric tests were used to determine intergroup differences. Results: 243 women delivered during this period. Although all had been booked before 18 weeks gestation, only 9% (n = 22) had been screened for ASB. Of the unscreened population, 18% (n = 40) subsequently developed a UTI in pregnancy, and these were more likely to deliver a LBW baby (18% <2500 g; OR 2.9, 95th CI 1.1–7.9). The screened population had rates of LBW (4%) which were the same as the unaffected cohort within the unscreened population (6%). Conclusion: These data suggest that a policy of not screening for ASB may increase the chance of LBW babies being born. Although other confounding variables were not controlled for in this study, the evidence would suggest a policy of screening for ASB remains a reasonable option in pregnancy. (supported by Cerebra).